Maintaining Mental Health during COVID-19 Pandemic: A Clinical Approach - Arshiya Masood Siddiqui; Arun Singh; Dvijendra Nath (Issues and Developments in Medicine and Medical Research Vol. 8, 2022)
New diseases have always been emerging and re-emerging and created panic and chaos among general public since ancient times. The current pandemic due to SARS-CoV-2 threatening the whole human race and due to this COVID-19 pandemic the fears, anxieties, stressors are dominating the communities of the globe. All media and channels have been discussing about all the kind of hopelessness like unavailability of effective treatment protocol, antiviral drugs and vaccines, there is panic all around the world. Among these uncertainties many institutions have been looking for the new ray of hope in the form of new antiviral drugs and vaccines against COVID-19. The humanities had faced such types of pandemics in the past and won the battle against these. Humanity and disease have always existed side by side [1]. Various pandemics e.g. influenza, plague, cholera and other infectious diseases have terrified the human from time to time but every time they have survived, won the battle, learnt a lesson and become better, stronger and creative. Until we get effective antiviral drugs and vaccines against COVID-19, the team PSM (Physical distancing, Sanitization of hands, equipment, surfaces, Masks) will work constantly against the COVID-19 and will play key role in stopping the transmission. The aims and objectives of this chapter are 1. To assess the problem of mental health and other dimensions of health during COVID-19 pandemic 2. To explore various ways to combat clinically the problem of mental health during COVID 19 pandemic.